Pengaruh E-WOM dan Brand Love Terhadap Loyalitas Merek Produk Fashion Generasi Z - Zai, Supriyaman; Rianto, Rianto; Qurniawati, Rina Sari (Jurnal Ilmiah Wahana Pendidikan, 2025)
Understanding how consumers of fashion products behave, especially generation Z, is important because they are the largest population today. This research will examine whether Social Media Marketing and brand love influence E-WOM and brand loyalty so that it can provide new insights for fashion product marketers. The method used is quantitative research using SEM-PLS. From this research it can be concluded that social media marketing has an influence on E-WOM. Apart from that, social media marketing and Brand Love have also been proven to influence brand loyalty